Strict liability in criminal law : a comparative approach - Kamaruddin, Zaleha (Nurin Enterprise, 1988)
This book was largely based on my dissertation submitted as partial fulfilment for Master of Comparative laws in International Islamic University. It is the aim of this book to highlight the lacunae in the common law concept of strict liability. Strict liability is a technical area of the law. Its apparent simplicity is complicated by many inconsistencies and anomalies within many of the statutory offences that form the bulk of its manifestations. I therefore offers shariah as solution to the problems manifested by strict liability